Penerapan Edukasi Kesehatan Bantuan Hidup Dasar untuk Meningkatkan Pengetahuan Karang Taruna dalam Menangani Cardiac Arrest - Ngaisus Suadak; Parmilah; Tri Suraning Wulandari (Jurnal Keperawatan Dan Kesehatan Holistik, 2026)
Cardiac arrest is a medical emergency that can occur anywhere; 73.9% of cases occur outside hospitals and are often witnessed by members of the public. In Balekerto Village, 9 of 10 members of the Karang Taruna (youth organization) did not know how to provide first aid for cardiac arrest, indicating a significant knowledge deficit regarding Basic Life Support (BLS). This study aimed to describe changes in the knowledge and skills of Karang Taruna members following health education on BLS. Using a qualitative descriptive design with a case study approach on three Karang Taruna members aged 16-30 years who had a BLS knowledge deficit, education was delivered over three sessions through lectures, demonstration, and re-demonstration. Data were collected using pre- and post-test questionnaires, a BLS standard operating procedure checklist, and the Indonesian Nursing Outcome Standard (SLKI) Knowledge Level indicator (L.12111). Results showed that all respondents experienced an increase in knowledge: Mr. R improved from 50% (poor) to 70% (moderate), while Mr. S and Mr. F improved from moderate to 80% (good). In terms of skills, Mr. S and Mr. F completed all 20 steps of the BLS procedure, while Mr. R completed 18 of 20 steps. The SLKI evaluation also showed improvement across all knowledge indicators. It is concluded that BLS health education through lectures, demonstration, and re-demonstration is effective in improving the knowledge and skills of Karang Taruna members in managing cardiac arrest in Balekerto Village.